To Render Invisible : Jim Crow and Public Life in New South Jacksonville - Cassanello, Robert (Book collections on Project MUSE., 2013)
An examination into the nature of social spaces that takes Jacksonville during Reconstruction as a case study, investigating the struggles and limitations of its Black and white working classes.